2018
DOI: 10.3390/nano8100794
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Nb2Se9 Molecular Chain from Bulk One-Dimensional Crystal by Liquid Exfoliation

Abstract: The optimum solvent for Nb2Se9 dispersion, which is a new type of one dimensional (1D) material, is investigated. Among several solvents (16 solvents in total), strong dispersion was observed in benzyl alcohol, isopropyl alcohol, isobutyl alcohol, and diacetone alcohol, which have medium dielectric constants in the range of 10 to 30 and surface tension in the range of 25 to 35 mJ m−2. 1D Nb2Se9 chains, whose size is less than 10 nm, are well dispersed and it is possible to disperse mono-chains of 1 nm or less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Bulk Nb 2 Se 9 has weak van der Waals interactions between unit chains and is a semiconductor with an indirect band gap based on DFT‐GGA (density functional theory with generalized gradient approximations) calculations . Recently we proved that the Nb 2 Se 9 crystals can be exfoliated to SCACs . In this letter, to investigate the potentially unique properties of our newly prepared 1D material, we calculated the electronic band structure of Nb 2 Se 9 chains by varying the number of chains in the bundles and predicting their unique electronic properties .…”
mentioning
confidence: 99%
“…Bulk Nb 2 Se 9 has weak van der Waals interactions between unit chains and is a semiconductor with an indirect band gap based on DFT‐GGA (density functional theory with generalized gradient approximations) calculations . Recently we proved that the Nb 2 Se 9 crystals can be exfoliated to SCACs . In this letter, to investigate the potentially unique properties of our newly prepared 1D material, we calculated the electronic band structure of Nb 2 Se 9 chains by varying the number of chains in the bundles and predicting their unique electronic properties .…”
mentioning
confidence: 99%
“…However, the dangling bonds on the edges in 2D materials still act as scattering centers 3 and recombination centers 4 when scaled down to less than a few tens of nanometers. In recent years, interest in 2D vdW materials has expanded to include one‐dimensional (1D) vdW structures comprising vdW‐bonded molecular chains 5–21 . There are two types of 1D vdW structures: a true 1D structure with a pure vdW interchain bond and a quasi‐1D structure with additional non‐vdW bonds among molecular chains.…”
Section: Introductionmentioning
confidence: 99%
“…To address the aforementioned problems, research has been conducted on the synthesis and application of chain-based layered materials, which can be used directly as quasi-1D conducting channels in a 2D vdWs heterostructure without an additional patterning process [14]. Several research groups have successfully demonstrated that Mo 6 S 9 – x I x [15], Nb 2 Se 9 [16,17,18], V 2 Se 9 [19,20,21,22], and TaSe 3 [14,23,24,25,26,27,28,29,30,31,32] consisting of multiple single molecular chains linked by weak vdWs interaction, can be exfoliated and used in electronic devices, optoelectronic devices, and energy storage devices. Recently, Balandin et al researched the trigonal prismatic TaSe 3 material, on which superconducting properties were observed decades ago [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Balandin et al researched the trigonal prismatic TaSe 3 material, on which superconducting properties were observed decades ago [14]. The authors found that this material had a high current-carrying capacity, and had the potential of being employed as an interconnector in electronic devices [18]. Shur et al further proved that the quasi-1D nanowires of TaSe 3 had lower levels of normalized noise spectral density, and had a potential for downscaled local interconnect applications [24,27,31].…”
Section: Introductionmentioning
confidence: 99%